Mechanical characterization and microstructure analyses of nano cellulose fiber biodegradable composite. (2021) - Siva, R.; Valarmathi, T.N.; Venkatesh, S.; Sathish Reddy, S.V.; Pandurangan, Prakash; Karthikeyan, P.
Abstract: Natural fiber composites are most effectively used nowadays, due to their low cost and biodegradability. In this work, 2% Nano Cissus quadrangularis fiber + 8% Cissus quadrangularis fiber and 10% Cissus quadrangularis fiber with polylactic acid as matrix material composites prepared through extrusion followed by injection molding. The mechanical properties tensile, flexural, and impact strength of both composites performed. The bonding characteristics of the fiber and polylactic acid analyzed by scanning electron microscope. The results revealed that 2% of Nano Cissus quadrangularis fiber + 8% Cissus quadrangularis fiber composites achieved higher mechanical properties than 10% Cissus quadrangularis fiber composite. Interestingly nanocomposite improved properties promise the best alternative for conventional natural composite usage in automobile, construction applications.